BRIDGING ECONOMIC SYSTEMS: A COMPARATIVE STUDY OF TAX STRUCTURES IN UZBEKISTAN AND JAPAN - Saidrasulov Ibrokhim Ikhtiyor ugli (Modern American Journals, 2025)
This study undertakes a comparative analysis of the tax and economic systems of Uzbekistan and Japan, with a particular focus on their structural frameworks, fiscal strategies, and recent policy reforms. The paper systematically explores the major components of each country’s taxation model, including corporate income tax, personal income tax, and consumption-based taxation, in order to understand how these mechanisms are employed to generate public revenue and maintain fiscal sustainability. By examining both countries’ approaches to tax administration and economic planning, the study identifies key differences in complexity, efficiency, and responsiveness to contemporary socio-economic challenges such as informality in Uzbekistan and population aging in Japan. While the primary emphasis lies on economic and fiscal policy, the paper also briefly touches upon the role of language education as a supportive tool for interpreting and teaching economic content, particularly in multilingual academic contexts. The findings of this research aim to provide valuable insights for economic educators, policy-makers, and researchers interested in international taxation and comparative public finance.
Keywords: Tax policy in Uzbekistan and Japan; Comparative tax systems; Corporate income tax; Personal income tax; Value-added tax (VAT); Economic development strategies